IMPLEMENTASI PROGRAM BERAS MISKIN (RASKIN) DI DESA SEJIRAM KECAMATAN SEBERUANG KABUPATEN KAPUAS HULU - Windha E.42008038 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
The title of this study is "Raskin Program Implementation in the Village District Sejiram Seberuang Kapuas Hulu" This study aims to determine how the implementation of the Program for the Poor Poor Rice Village Sejiram Seberuang Kapuas Hulu district that has implemented the village government from 1999 through 2012 with focus on the implementation of the distribution of Raskin to the distribution point. This title Program Implementation issues raised by Rice for the Poor in Poor Rural Sejiram Seberuang Kapuas Hulu district that still has not been done up. Researchers using qualitative analysis, policy research through the three stages of data collection, data analysis and conclusion. What research is in the Village Sejiram, Seberuang District, Kapuas Hulu. Subjects were Secretary Head, Head of Public Welfare, the Village Head, Village Head and the people living in the village Sejiram. The conclusion of this research is the distribution of rice for the poor for the poor is not timely in the distribution of rice for the poor, due to no communication and resources made by the party entitled to distribute this poor rice. For it is in the implementation of the policy pursued by the government should be socialized from Central, provincial, district, sub-district, village and the hamlet, and the people who receive the benefits Raskin.Keywords: Implementation, Program Raskin.